2016
DOI: 10.1371/journal.pone.0159740
|View full text |Cite
|
Sign up to set email alerts
|

Pullulanase Is Necessary for the Efficient Intracellular Growth of Francisella tularensis

Abstract: Pullulanase, an enzyme that catalyzes the hydrolysis of polysaccharides, has been identified in a broad range of organisms, including bacteria, yeasts, fungi, and animals. The pullulanase (pulB; FTT_0412c) of F. tularensis subspecies tularensis Schu S4 is considered to be a homologue of the type I pullulanase (pulA) of the other Francisella subspecies. The significance of Francisella pullulanase has been obscure until now. In the present study, we characterized a recombinant PulB of F. tularensis SCHU P9, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Bacterial loads were quantified by inoculating 100 μL of homogenates of infected lungs, spleens and livers diluted in RPMI 1640 onto Eugon chocolate agar plates, as previously reported . After cultivation at 37°C for 4 days, CFUs were calculated by multiplying the average number of colonies by 10 to account for the dilution factor.…”
Section: Methodsmentioning
confidence: 99%
“…Bacterial loads were quantified by inoculating 100 μL of homogenates of infected lungs, spleens and livers diluted in RPMI 1640 onto Eugon chocolate agar plates, as previously reported . After cultivation at 37°C for 4 days, CFUs were calculated by multiplying the average number of colonies by 10 to account for the dilution factor.…”
Section: Methodsmentioning
confidence: 99%
“…Pullulanase can catalyze the hydrolysis of polysaccharides, and it has been identified in a broad range of organisms, such as bacteria, yeasts, fungi, and animals. 42 However, there are few studies on its function in pathogenic bacteria. Akihiko et al showed that pullulanase is necessary for the efficient growth of Francisella tularensis in macrophages but does not contribute to bacterial virulence in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Akihiko et al showed that pullulanase is necessary for the efficient growth of Francisella tularensis in macrophages but does not contribute to bacterial virulence in vivo. 42 Bueren et al 43 considered pullulanase a potential virulence factor for pathogenic streptococci. They found that pullulanase surface anchored by S. pneumoniae and S. pyogenes could bind to alveolar type II cells in mouse lung tissue, leading to a stronger reaction between the pathogen and the host cells.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that the ∆ pdpC mutant strain had the potential to protect mice from lethal intranasal challenge with a virulent strain via subcutaneous immunization 34 . The pdpC gene of the virulent strain SCHU P9 was disrupted by group II intron insertion using the TargeTron gene knockout system 37,38 to generate the Δ pdpC mutant strain 39 . Thus, the genetic stability of strain ∆ pdpC was confirmed by in vivo passages in mice for 10 generations 34 .…”
Section: Discussionmentioning
confidence: 99%